Gaps in translation from trials to practice: Non-vitamin K antagonist oral anticoagulants (NOACs) for stroke prevention in atrial fibrillation - Hylek, Elaine M.; Ko, Darae; Cove, Christina L. (Thrombosis and Haemostasis, 2014)
Worldwide there is a tremendous need for affordable anticoagulants that do not require monitoring. The advent of the non-warfarin oral anticoagulant drugs represents a major advance for stroke prevention in atrial fibrillation (AF). The objectives of this review are to 1) identify gaps in our current knowledge regarding use of these single target anticoagulant drugs; 2) outline the potential implications of these gaps for clinical practice, and thereby, 3) highlight areas of research to further optimise their use for stroke prevention in AF.